Russia´´´ s strategic personality and its influence on the relation with the West. - HAPCHYN, Sofiya (Journal of the Spanish Institute for Strategic Studies, 2022)
Since 1991, the relationship between Russia and the West was marked by cooperation and competition. While in the first years of the newly formed Federation the ideas of the westernizers prevailed, the (neo)eurasianist postulates dominate the current national discourse, leading to stagnation in its relationship with the West. Such ideological reorientation is the result of external shocks in the international system, as well as internal. In this work, the main Russian and Western schools of thought are analyzed, contrasting them to explain, from the perspective of Neoclassical realism, the perception and behavior of Moscow, in relation to Western countries, at different stages in the global arena.
Keywords: Russia, the West, strategic personality, Westernism, (Neo)Eurasianism.